Socio‐Economic and Gender Differences in Post‐Secondary Pathways in the UK, Germany, and Australia - Wojtek Tomaszewski; Hans Dietrich; Golo Henseke; Ning Xiang; Ingrid Schoon (Social Inclusion)
This study investigates variations in school‐to‐work transitions (SWTs) by socio‐economic status (SES), gender, and socio‐cultural context. Leveraging data from three nationally representative longitudinal panel studies, we compare the experiences of young people coming of age in the 21st century (2011 to 2023) in the United Kingdom, Germany, and Australia. We examine the role of different support systems that scaffold the SWT process along various post‐secondary pathways, including university, further education/vocational training, and employment tracks, with a particular focus on variations by parental education and gender. Utilizing longitudinal data from the Understanding Society Panel in the UK (N = 15,692 observations), the German Socio‐Economic Panel (GSOEP; N = 5,464), and the Household, Income and Labour Dynamics in Australia (HILDA) Survey (N = 5,759), we track synthetic cohorts born between 1993 and 1995 from ages 18 to 27 in the three countries. We employ linear probability models to conduct a cross‐national comparative analysis, identifying variations in post‐secondary pathways across the three country contexts. The choice of countries is motivated by their shared status as developed economies with distinct features in their SWT systems—contrasting the neoliberal deregulatory frameworks of Britain and Australia with Germany’s employment‐focused dual system. The findings reveal significant effects of parental education on post‐secondary transitions, as well as the differing roles of gender across various educational policy contexts. These results underscore the complexity of SWT when considered in different national settings. The insights generated by this analysis highlight the importance of dedicated policies to support low‐SES youth and promote gender equality in education and employment outcomes.